Strategi Pemeliharaan dan Perawatan Sistem Irigasi di Desa Patane V - Bijak Bijak; Eben Zai; Dapot Dapot; Brain Brain; Ebenezer Ebenezer; Efraim Efraim (Karawo : Journal of Community Service (KJCS), 2025)
Irrigation systems play an important role in supporting agricultural productivity, especially in rural areas such as Patane V Village. However, without adequate maintenance and care, irrigation efficiency can decrease, causing decreased agricultural yields and potential environmental damage. This study aims to identify irrigation system maintenance and care strategies that can be applied effectively in Patane V Village. The methods used are direct field observation and cleaning and interviews with farmers and related parties. The results of the study indicate that regular maintenance, community participation, and the use of simple technology in cleaning irrigation channels are key factors in maintaining the sustainability of the irrigation system. This study is expected to provide recommendations for village governments and farmer groups in managing irrigation systems more effectively.